HUBUNGAN MINAT MEMBACA BUKU KIA DENGAN PENGETAHUAN IBU HAMIL TENTANG BUKU KIA - Faradina Nur Annisa (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
Maternal Mortality Rate (MMR) in Indonesia is still high relatively, recent data from the World Health Organization in 2011 the MMR in Indonesia is 240/100 thousands birth rate. One of the eff ort developed by Ministry of Health is empowering families and people by KIA book. KIA book is an important book for pregnant mothers. One of way to get knowledge well, a person must have an interest to read. This research aimed for knowing the relationship between reading interest of KIA book with pregnant mothers knowledge about KIA book. Research This research used analytic observational with cross sectionalapproach. Population in this research is all of pregnant mothers in the 2nd and 3rd semester that have KIA book in Rural Clinic Pulungdowo Tumpang, with the amount of population is 36 people. Sample taking use purposive sampling technique with the number of 33 people. Data processing displayed in thefrequency distribution table and analyzed using Spearman Rank correlation test, research result shows that half of respondent, 33.3% has high interest and well knowledge. Based Spearman Rank test with signifi cance level 0.05, obtained signifi cance value 0.000  0.05, it means that there is a relationship between reading interest of KIA book with pregnant mothers knowledge about KIA book.Keywords: Reading interest, Pregnant mothers, KIA book, Knowledge